Inhibitory Effect of Eugenol and trans‐Anethole Alone and in Combination with Antifungal Medicines on Candida albicans Clinical Isolates. Issue 5 (15th April 2021) - Dąbrowska, Marta; Zielińska‐Bliźniewska, Hanna; Kwiatkowski, Paweł; Łopusiewicz, Łukasz; Pruss, Agata; Kostek, Mateusz; Kochan, Ewa; Sienkiewicz, Monika
Abstract: One of the most common pathogens among yeasts is Candida albicans, which presents a serious health threat. The study aimed to check the antifungal properties of trans‐ anethole and eugenol with selected antifungal medicines (AMs) against C. albicans clinical isolates. The checkerboard method was used to tests of interactions between these compounds. Achieved results indicated that eugenol showed synergistic and additive activities with miconazole and econazole against investigated clinical isolates, respectively. Moreover, the combination – trans‐ anethole – miconazole also showed an additive effect against two clinical isolate. We tried to relate the results to changes in C. albicans cell sheaths under the influence of essential oils compounds (EOCs) performing the Fourier transform infrared spectra analysis to confirm the presence of particular chemical moieties in C. albicans cells. Nevertheless, no strong relationships was observed between synergistic and additive actions of used EOC‐AMs combinations and chemical moieties in C. albicans cells. Abstract :